Principle of Freedom of Contract in On-Line Trade Transactions (E-Commerce) (Comparison of Civil Law System, Common Law System and Islamic Law System) - Any Farida (Proceeding International Conference Restructuring and Transforming Law, 2023)
Advances in computer and internet technology, as well as cyberspace, facilitate relationships between humans, including trade transactions.The transaction process carried out in the business world without any meetings between the parties is called electronic commerce. E-commercewhich is carried out through the exchange of information without a physical meeting of the parties, raises very basic problems and requires reconstruction of the theory of contract law, namely: How to implement the principle of freedom of contract in e-commerce transactionsand the limitations according to the civil law system, common law system and Islamic law system? This research was carried out using a normative juridical approach (doctrinal research), with descriptive comparative legal research specifications. The data collection method used is literature study, data analysis using deductive analysis methods.The principle of freedom of contract in transactionse-commerceaccording to the legal systemcivil law system, common law systemAndIslamic law systemcan be implemented properly, even though in general it is a standard contract whose contents and format have been created and prepared by one of the parties (seller/merchants). This freedom of contract is seen when there is an agreement between the seller/merchantswith buyers/consumers who are indicated by filling in the order form provided by the seller/merchantsand “click” of approval by the buyer/consumer. The transaction continues with payment via transfer and delivery of goods via courier which can be proven by a receipt for the transfer and delivery of goods. Freedom of contract is limited by state law, viz does not conflict with the law, decency and public order. Meanwhile, according to Islamic law, transactionse-commerceequated with buying and selling orders (Greetings)and the law is permissible (permissible) which must be based on mutual consent (without compulsion), implemented with true intentions (sincere, good faith), not detrimental to other parties and beneficial.